Limit theorems for linear processes generated by ρ-mixing sequence. Issue 17 (9th August 2021) - Tang, Zhiqiang; Zhang, Yong
Abstract: Let ξ i, i ∈ Z be a strictly stationary ρ -mixing sequence of non degenerate random variables with zero means. In this paper, we study the central limit theorem and almost sure central limit theorem for self-normalized partial sums of linear processes generated by ξ i, i ∈ Z .